Reduction in energy consumption and CO2 emissions by retrofitting an existing building to a net zero energy building for the implementation of SDGs 7 and 13 - Razzaq, Ibtisam; Amjad, Muhammad; Qamar, Adnan; Asim, Muhammad; Ishfaq, Kashif; Razzaq, Afia; Mawra, Khadija (Frontiers in Environmental Science, 2023)
This work aims to reduce the energy consumption of existing buildings through retrofitting and converting them into net zero energy buildings (NZEBs). Various retrofits for an existing academic building were modeled and analyzed using REVIT software. Energy consumption was reduced to approximately 34% through retrofits, and a Solar System of 41.6 kW was integrated to meet the reduced energy demand, consequently converting the building into an net zero energy building (NZEB). Furthermore, environmental and economic analyses were conducted, and the results show a reduction of 32.8 metric tons of CO2 emissions per year as a result of retrofitting the building, converting it into an net zero energy building. The building envelope retrofits and electrical appliances have a payback period of 2.96 and 2.62 years, respectively, whereas the proposed Solar System has a payback period of only 2.3 years. Moreover, the building was rated using the Leadership in Energy and Environmental Design (LEED) rating tool, and it qualifies for silver certification after retrofits and the integration of renewable energy sources (RES). The reduction in energy consumption and integration of renewable energy sources contribute to achieving Sustainable Development Goal (SDG) 7, and reduced CO2 emissions save climate variations, which leads to achieving Sustainable Development Goal 13.